A Patterned Butyl Methacrylate-co-2-Hydroxyethyl Acrylate Copolymer with Softening Surface and Swelling Capacity - León Boigues, Laia (2019)
The tunable swelling and mechanical properties of nanostructures polymers are crucial parameters for the creation of adaptive devices to be used in diverse fields, such as drug delivery, nanomedicine, and tissue engineering. We present the use of anodic aluminum oxide templates as a nanoreactor to copolymerize butyl methacrylate and 2-hydroxyethyl acrylate under radical conditions. The copolymer obtained under confinement showed significant differences with respect to the same copolymer obtained in bulk conditions. Molecular weights, molecular weight dispersities, Young’s modulus, and wetting behaviors were significantly modified. The combination of selected monomers allowed us to obtain nanopillar structures with an interesting softening surface and extraordinary swelling capacity that could be of special interest to surface science and specifically, cell culture.